Understanding multiple health risks for low-income communities in Cape Town: water stress, COVID-19, and climate change - Foggitt, Alice (Department of Environmental and Geographical Science, 2022)
Climatic hazards, such as flooding and drought, are expected to increase in frequency as a result of climate change. Growing evidence suggests that climate-induced water challenges will interact with health concerns, compounding pre-existing challenges for vulnerable populations in low-and middle-income contexts. Due to the novel nature of COVID-19, limited research has focused on the combined impact of the climate crisis and COVID-19 on human health, particularly in South Africa. Thus, there is an urgent need to enhance understanding of the adverse health impacts linked to climate-related water stressors. Using a mixed-methods approach, this study drew upon multiple datasets to explore water-related health risks prevalent during the Cape Town drought, and in the subsequent period up to and including the current COVID-19 pandemic. Data sources include qualitative stories from a community resilience project, video interviews from the drought response in Cape Town, quantitative COVID-19 water service delivery data from informal settlements, and a document analysis of the Cape Town Water Strategy. Data was analysed using inductive and deductive research approaches to piece together different perspectives on how the pandemic interacts with pre-existing hazards. The study uses the climate-water-health nexus framing to investigate some of the critical health risks present during and after the drought. The study also explores how the COVID-19 pandemic interacted with health and water issues, providing a snapshot of the lived experience of the urban poor during an emerging public health crisis. The study subsequently considers the implications for the Cape Town water sector in view of the drought and ongoing COVID-19 pandemic. Results from this study show that inadequate sanitation and exposure to wastewater are the most commonly cited health risks for low-income households in the study sites. The COVID-19 pandemic has amplified existing water-associated health risks by indirectly widening health inequalities and increasing poverty levels. Moreover, compound risks have limited the ability of low-income households to cope with additional shocks and stressors. The findings of this study contribute to a critical research gap and expand the evidence base on the relationship between climate change, water, health, and compound risks in the South African context. The study calls for the adoption of a cross-sectoral, integrated approach to address health threats at the climate-water-health nexus.